Caracterização físico-mecânica de duas espécies de madeira amazônicas proveniente do 2º ciclo de corte da Floresta Nacional do Tapajós - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2016)
In the Brazilian Amazon the diversity of potentially producing tropical wood species is very wide, but the timber commercial exploitation focuses on a small group of species, due to changes in forest dynamics constadas after first exploration, species little explored in the past becomes dominant, but the lack of technological knowledge makes it difficult to use the same, and the physical and mechanical properties are essential to assist you properly define your applications. Hereby this study aimed to perform the physical-mechanical characterization of Eschweilera ovata and Pseudopiptadenia psilostachya the 2nd cutting cycle of the Tapajós National Forest, aiming to commercially promote and indicate new possibilities of use to them and evaluate replacement feasibility species highly marketed. For the realization of physical and mechanical tests, we selected five individuals of each species for making the specimens according to NBR 7190.The Mata-Matá Jibóia (Eschweilera ovata) basic density of 0.80 g / cm3; MOR 127.1 Mpa; MOE 17870 Mpa. And Fava-Timborana (Pseudopiptadenia psilostachya) basic density of 0.68 g / cm3; MOR 137.2 Mpa; MOE 15593 Mpa, similarities in these properties allows the use of these varied species studied, from these results found in this study, it was concluded that although unknown species showed wood with sufficient quality to be used commercially.
Keywords: Densidade básica; Tecnologia da Madeira; Manejo Sustentável de impacto reduzido.; CNPQ:: ENGENHARIAS